Temporal trend in early sepsis in a very low birth weight infants' cohort: an opportunity for a rational antimicrobial use - Jamil Pedro de Siqueira Caldas; Lorenna Cristina Montera; Roseli Calil; Sergio Tadeu Martins Marba (Elsevier, 2021)
Objective: This study aimed to evaluate annual trends of early neonatal sepsis and antimicrobial use in very low birth weight infants for 12 years, as well as to identify microbiological agents, antimicrobial sensitivity profiles, and association with early neonatal death. Method: This was a retrospective cohort study including 1254 very low birth weight infants admitted from 2006 to 2017. Four groups were evaluated: culture-confirmed sepsis; presumed neonatal sepsis; ruled out neonatal sepsis group; and infants not exposed to antibiotics. Results: The medians of gestational age and birth weight were 29 weeks (27-31) and 1090 g (850-1310), respectively. The rates of culture-confirmed sepsis, presumed neonatal sepsis, ruled out neonatal sepsis, and not exposed to antibiotics were 1.3, 9.0, 15.4, and 74.3%, respectively. From the initial group of newborns whose antimicrobial treatment was administered for sepsis' suspicion, it was possible to discontinue antibiotic in 44%. The culture-confirmed sepsis rates remained stable (p = 0.906). Significant tendencies of decreasing presumed sepsis rates (p < 0.001) and increased ruled out neonatal sepsis/not exposed to antibiotics rates (p < 0.001) were observed. Streptococcus agalactiae and enteric Gram-negative rods were the predominant agents and most of them were sensitive to crystalline penicillin/ampicillin (88.2%) and to ampicillin and/or amikacin. Early death occurred in 10.8%, specifically in the culture-confirmed sepsis and presumed neonatal sepsis groups. Conclusion: The confirmed sepsis rate was low and remained stable. There was a significant downward trend in the presumed neonatal sepsis rate and a significant upward trend in the ruled out neonatal sepsis group. The rate of not exposed to antibiotics infants was high, also presenting a significant downward trend. The identified bacteria were those commonly found and showed usual antimicrobial susceptibility patterns. Death predominantly occurred in groups that received antibiotic treatment.